1979
DOI: 10.3758/bf03209712
|View full text |Cite
|
Sign up to set email alerts
|

Approach-avoidance conflict in preweanling rats: A developmental study

Abstract: Ten-and lfi-day-old rat pups were trained with two procedures to approach an anesthetized mother, and then were punished for approaching. Both ages of subjects exhibited increased latencies to reapproach the mother, indicating passive inhibitions, but only the older pups retreated. All but one of the younger pups eventually reached the mother within 3 min after the punishment, while only half of the older pups did so. In a second experiment examining the development of locomotor avoidance reactions, 5· to 20-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 10 publications
4
38
0
Order By: Relevance
“…Indeed, before showing a slow linear volumetric increase until 7 months of age, the central nucleus exhibits early exponential growth between 1 and 2 weeks of age. Functional studies have shown that flight reactions are not present in 5-day-old rat pups, are still weak at 10 days of age, but are largely mature at 15 days of age (Collier et al, 1979). Freezing in response to a conditioned stimulus appears at P10 in rats (Sullivan, 2001).…”
Section: Functional Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, before showing a slow linear volumetric increase until 7 months of age, the central nucleus exhibits early exponential growth between 1 and 2 weeks of age. Functional studies have shown that flight reactions are not present in 5-day-old rat pups, are still weak at 10 days of age, but are largely mature at 15 days of age (Collier et al, 1979). Freezing in response to a conditioned stimulus appears at P10 in rats (Sullivan, 2001).…”
Section: Functional Considerationsmentioning
confidence: 99%
“…Individual components of the fear response are thought to incorporate sequentially as animals mature, eventually giving rise to what are identified as mature fear behaviors (Wiedenmayer, 2009). Indeed, several studies have revealed that distinct fear behaviors emerge at different times during early postnatal life and continue to mature during late postnatal development (Blozovski and Cudennec, 1980;Bronstein and Hirsch, 1976;Chen et al, 2006;Collier et al, 1979;Foster and Burman, 2010;Hefner and Holmes, 2007;Hubbard et al, 2004;Ito et al, 2009;Kim and Richardson, 2007;Moriceau et al, 2004;Raineki et al, 2010;Rudy, 1993;Takahashi, 1992;Wiedenmayer andBarr, 1998, 2001a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Predator odor-induced freezing and coincident amygdala activation can be evoked precociously by injecting CORT in sensitive-period pups (Takahashi et al, 1991;Takahashi, 1992;Weidenmayer and Barr, 2001;Moriceau et al, 2004). Third, adrenalectomizing pups can prolong the infants' unique sensitive-period learning, such as attenuated fear and inhibitory conditioning (Collier et al, 1979;Blozovski and Cudennec, 1980;Bialik et al, 1984;Myslivecek, 1997;Moriceau and Sullivan, 2004b), as well as extend the learning-induced changes of the olfactory bulb characteristic of the sensitive period (Moriceau and Sullivan, 2004b). Fourth, sensitive-period odor-shockinduced preference learning and its olfactory bulb neural correlates can be blocked by a single injection of CORT, although pups did not learn to avoid the odor (Moriceau and Sullivan, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when paired with odor , LiCI may serve as a punisher and fixate the approach response to odor . There is, in fact, evidence that punishment does tend to fixate the approach response to familiar nest odors and other horne environmental stimuli (Collier, Mast, Meyer, &Jacobs, 1979;Peterson, Benton, Gordon, Misanin, & Hinderliter, 1985). Collier et al (1979) found rat pups to continue to approach a darn even though they were punished for doing so, and Peterson et al .…”
Section: Discussionmentioning
confidence: 99%
“…There is, in fact, evidence that punishment does tend to fixate the approach response to familiar nest odors and other horne environmental stimuli (Collier, Mast, Meyer, &Jacobs, 1979;Peterson, Benton, Gordon, Misanin, & Hinderliter, 1985). Collier et al (1979) found rat pups to continue to approach a darn even though they were punished for doing so, and Peterson et al . (1985) reported that preweanlings persisted in running to homecage shavings located in the nonreinforced endbox in an aversively motivated spatial discrimination task.…”
Section: Discussionmentioning
confidence: 99%